The heir, the franchisor, and the coffee barista: Socio-spatial trajectories of migrantwomen entrepreneurs in street vending - Ojeda, Lautaro; Margarit Segura, Daisy; De La Barra Astudillo, Victoria (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2025)
Between the years 2017 and 2024, the Venezuelan migrant population arrived on a larger scale to Chile. In the area of informal economy, in 2024 they became the 46% of the country’s informal migrant workforce, constituting 33% of all street vendors. For migrants, informal work tends to be the first and, often, only door for job placement in the country of arrival, which implies labor exploitation, financial instability, absence of social rights, and in the case of informal street vending, conflicts and costs related to the daily use of public spaces. This article problematizes the relation between socio-territorial networks, human structures, urban contexts and how this relation shapes the entrepreneurship of Venezuelan migrants that work in three neighborhoods in the Metropolitan Region and Valparaíso in Chile.